Estimating multidimensional childhood poverty in the Democratic Republic of Congo, 2007 through 2013 - Kristi Mahrt; Malokele Nanivazo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
After years of economic decline, conflict, and instability, the Democratic Republic of Congo achieved rapid economic growth in the 2000s along with a reduction in rural consumption poverty. This paper evaluates the extent to which recent growth has been accompanied by improvements in multidimensional child welfare using a first-order dominance approach applied to Multiple Indicator Cluster Surveys and Demographic and Health Surveys. The authors explore the root of indeterminate outcomes in spatial analysis and evaluate the sensitivity of spatial and temporal outcomes to indicator choice. Though results do not indicate broad-based welfare advancement at the national, urban, or rural levels, they do suggest progress within a number of individual provinces.
Keywords: C81; I 32; J13; 330; welfare; first-order dominance; Democratic Republic of Congo; multidimensional poverty; children